Droplet bubbling evaporatively cools a blowfly - Gomes, Guilherme; Köberle, Roland; Von Zuben, Claudio J. [UNESP]; Andrade, Denis V. [UNESP] (Springer Nature, 2018)
Terrestrial animals often use evaporative cooling to lower body temperature. Evaporation can occur from humid body surfaces or from fluids interfaced to the environment through a number of different mechanisms, such as sweating or panting. In Diptera, some flies move tidally a droplet of fluid out and then back in the buccopharyngeal cavity for a repeated number of cycles before eventually ingesting it. This is referred to as the bubbling behaviour. The droplet fluid consists of a mix of liquids from the ingested food, enzymes from the salivary glands, and antimicrobials, associated to the crop organ system, with evidence pointing to a role in liquid meal dehydration. Herein, we demonstrate that the bubbling behaviour also serves as an effective thermoregulatory mechanism to lower body temperature by means of evaporative cooling. In the blowfly, Chrysomya megacephala, infrared imaging revealed that as the droplet is extruded, evaporation lowers the fluids temperature, which, upon its re-ingestion, lowers the blowfly's body temperature. This effect is most prominent at the cephalic region, less in the thorax, and then in the abdomen. Bubbling frequency increases with ambient temperature, while its cooling efficiency decreases at high air humidities. Heat transfer calculations show that droplet cooling depends on a special heat-exchange dynamic, which result in the exponential activation of the cooling effect.